40 lines
767 B
TeX
Raw Normal View History

2022-11-13 13:31:00 -08:00
\documentclass[../main.tex]{subfiles}
\begin{document}
\problem{An Elephant and a Mosquito}
Does the weight of an elephant equal the weight of a mosquito? Let $x$ be the weight of an elephant, and $y$ that of a mosquito.
\begin{figure}[h]
\centering
\includegraphics[width=10cm]{252}
\end{figure}
Call the sum of the two weights $2v$, then $x + y = 2v$.
From this equation we can obtain two more:
\[
x - 2v = -y \text{; } x = - y + 2v
\]
Multiply:
\[
x^2 - 2vx = y^2 - 2vy
\]
Add $v^2$:
\[
x^2 - 2vx + v^2 = y^2 - 2vy + v^2 \text{, or } (x - v)^2 = (y - v)^2
\]
Take square roots:
\[
x - v = y - v \text{; } x = y
\]
That is, the elephant's weight ($x$) equals the mosquito's weight ($y$). What is wrong here?
\end{document}